Book Donation and Exchange as Sources of Collection Development in Nigerian University of Lagos Library Experience (Journal of Science and Technology, 2016)
It is generally acknowledged that access to appropriate reading and information is essential for political, educational, social and economic development. Libraries in Nigeria, however, do not have the books and materials they require due to financial constraints. This paper discusses some critical issues for collection development through book donations and exchange contribution of books to Nigerian University Libraries with special reference to University of Lagos Library. It also makes recommendation for the development of selected existing book donation schemes.